PENGARUH HAFALAN AL QURAN TERHADAP PRESTASI AKADEMIK DAN NON AKADEMIK SISWA MTS SALAFIYAH MOJOGENENG JATIREJO MOJOKERTO - Sani Zakariyah, Faisal (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2024)
This study aims to determine the effect of memorising the Qur'an on students' academic and non-academic achievements. The research method used is quantitative research with a descriptive approach, namely a research method based on the philosophy of positivism, used to examine certain populations or samples, data collection using research instruments, quantitative / statistical data analysis. Based on the calculation of the formula above, the sample in this study was 109 respondents. The results showed that respondents with sufficient memorisation were respondents with academic achievement in the sufficient category 33.0%, while respondents with less memorisation were respondents with good academic achievement 19.3% and sufficient academic achievement 13.8%. Based on the results of the regression test, it is known that the significant value of 0.560> alpha 0.05 means that there is no effect of memorising the al quran on the academic achievement of VIII students of Mts Salafiyah Mojogeneng in 2023. respondents with good memorising the al quran have good non-academic achievement 18.3% and respondents with less memorising have less non-academic achievement 3.7%. Based on the results of the regression test, it is known that the significant value of 0.000 < alpha 0.05 means that there is an effect of memorising the Qur'an on the non-academic achievement of VIII students of Mts Salafiyah Mojogeneng in 2023.